Unraveling the Role of Dopaminergic and Calretinin Interneurons in the Olfactory Bulb - Capsoni, Simona; Fogli Iseppe, Alex; Casciano, Fabio; Pignatelli, Angela (Frontiers in Neural Circuits, 2021)
The perception and discriminating of odors are sensory activities that are an integral part of our daily life. The first brain region where odors are processed is the olfactory bulb (OB). Among the different cell populations that make up this brain area, interneurons play an essential role in this sensory activity. Moreover, probably because of their activity, they represent an exception compared to other parts of the brain, since OB interneurons are continuously generated in the postnatal and adult period. In this review, we will focus on periglomerular (PG) cells which are a class of interneurons found in the glomerular layer of the OB. These interneurons can be classified into distinct subtypes based on their neurochemical nature, based on the neurotransmitter and calcium-binding proteins expressed by these cells. Dopaminergic (DA) periglomerular cells and calretinin (CR) cells are among the newly generated interneurons and play an important role in the physiology of OB. In the OB, DA cells are involved in the processing of odors and in the adaptation of the bulbar network to external conditions. The main role of DA cells in OB appears to be the inhibition of glutamate release from olfactory sensory fibers. Calretinin cells are probably the best morphologically characterized interneurons among PG cells in OB, but little is known about their function except for their inhibitory effect on noisy random excitatory signals arriving at the main neurons. In this review, we will mainly describe the electrophysiological properties related to the excitability profiles of DA and CR cells, with a particular view on the differences that characterize DA mature interneurons from cells in different stages of adult neurogenesis.